Erythropoietin administration alone or in combination with endurance training affects neither skeletal muscle morphology nor angiogenesis in healthy young men. Issue 10 (1st October 2014) - Larsen, Mads S.; Vissing, Kristian; Thams, Line; Sieljacks, Peter; Dalgas, Ulrik; Nellemann, Birgitte; Christensen, Britt
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Is an erythropoiesis‐stimulating agent (ESA), alone or in combination with endurance training, able to induce changes in human skeletal muscle fibre and vascular morphology? What is the main finding and its importance? Human skeletal muscle morphology and angiogenetic effects did not exhibit sensitivity to ESA treatment alone. Endurance training stimulates angiogenesis and fibre type transition in the direction of a more oxidative fibre phenotype; however, addition of ESA had no further effect. The aim was to investigate the ability of an erythropoiesis‐stimulating agent (ESA), alone or in combination with endurance training, to induce changes in human skeletal muscle fibre and vascular morphology. In a comparative study, 36 healthy untrained men were randomly dispersed into the following four groups: sedentary–placebo (SP, n = 9); sedentary–ESA (SE, n = 9); training–placebo (TP, n = 10); or training–ESA (TE, n = 8). The ESA or placebo was injected once weekly. Training consisted of progressive bicycling three times per week for 10 weeks. Before and after the intervention period, muscle biopsies and magnetic resonance images were collected from the thigh muscles, blood was collected, body composition measured and endurance exercise performance evaluated. The ESA treatment (SE and TE) led to elevated haematocrit, and both ESA treatment and training (SE, TP and TE) increased maximal O2 uptake. With regard to skeletal muscle morphology, TP alone exhibited increases in whole‐muscle cross‐sectional area and fibre diameter of all fibre types. Also exclusively for TP was an increase in type IIa fibres and a corresponding decrease in type IIx fibres. Furthermore, an overall training effect (TP and TE) was statistically demonstrated in whole‐muscle cross‐sectional area, muscle fibre diameter and type IIa and type IIx fibre distribution. With regard to muscle vascular morphology, TP and TE both promoted a rise in capillary to muscle fibre ratio, with no differences between the two groups. There were no effects of ESA treatment on any of the muscle morphological parameters. Despite the haematopoietic effects of ESA, we provide novel evidence that endurance training rather than ESA treatment induces adaptational changes in angiogenesis and muscle morphology.